Three‐dimensionally Ordered Macro‐porous Metal‐organic Framework for High‐performance Lithium‐sulfur Battery. Issue 1 (12th January 2022) - Wang, Tong; Liu, Yanyu; Liu, Xin; Cui, Guoliang; Zhang, Yongguang; Wang, Xin
Abstract: The commercial application of lithium‐sulfur (Li−S) battery is greatly hampered by the shuttling of lithium polysulfide (LiPS). In this work, a double‐solution‐induced method is proposed to synthesize multifunctional three‐dimensionally ordered macro‐micro porous MOFs (3DOM ZIF67) as an efficient promotor to achieve excellent electrochemical performance. The unique ordered macro‐porous structure not only accelerates ion diffusion and charge transfer, but also enlarges the active interfaces. In addition, the nanometric ZIF67 unit with high porosity can achieve strong sulfur immobilization and catalysis by chemical interaction with LiPS, which vastly inhibited shuttle effect and promoted the rapid redox kinetics. As expected, the S/3DOM ZIF67 cathode achieves a high capacity of 920.7 mAh g −1 at 1.0 C and excellent cycle performance over 500 cycles. This design offers a feasible way to develop MOF‐based materials with efficient adsorption and electrocatalysis for high‐performance Li−S battery. Abstract : A 3D ordered hierarchical porous 3DOM ZIF67 has been developed as advanced sulfur host materials. The unique structure provides multiple spatial confinements for LiPS trapping and buffers volume variation during cycling. Meanwhile, abundant exposed cobalt metal ions can efficiently adsorb and transform the LiPS, which promoted the rapid redox kinetics.